Effect of Maximum Heart Rate on Accuracy of Fire - Richard Billich; Erik Barták; Jiří Beneš; Petr Majerčík; Karel Jelen (Karolinum Press, 2015)
In today's world, when many offenders are well-equipped with firearms and ready to use them to avoid their apprehension, when the threat of a terrorist attack is high, when war conflicts are increasingly conducted within city borders (urban warfare), the skill of precise and quick elimination of an enemy is vital for members of law enforcement agencies operating in physically demanding situations. The goal of this paper is to examine the effect of maximum heart rate on the pistol shooting performance by analyzing precision target shooting data of a set of 8 participants all coming from the ranks of the Police of the Czech Republic. This paper represents an empirical descriptive study. In order to find out statistical significance, we used the statistical method of a paired two-sample t-test. We organized the collected data by comparing arithmetic means. For grouping and interpretation of target shooting data, we utilized the method of finding the central point of shots at a target. The Sport tester, a monitoring device, helped provide the values of maximum heart rate. Based on the data collected, we conclude that maximum heart rate has a statistically significant effect on precision of target shooting. This precision was defined by the average distance of individual shots at a target from the central point of impact. We also found that the size of this distance before and after intense physical activity can be influenced sport activities that respondents perform as their hobbies.